Recent advances in cataluminescence gas sensor: Materials and methodologies. Issue 4 (21st April 2019) - Hu, Jiaxi; Zhang, Lichun; Lv, Yi
ABSTRACT: Cataluminescence (CTL), one kind of the chemiluminescence, generates on the surface of solid catalyst during a heterogeneous catalytic oxidation reaction with the advantages of high sensitivity, fast response, simple instrument and longtime stability. This review provides the advances in CTL, mainly discussed the developments of sensing materials, detection technologies and application of CTL in recent 3 years. Also, we proposed various prospects and expectations of CTL-based sensor system at the end of this paper.